Proangiogenic Features of Mesenchymal Stem Cells and Their Therapeutic Applications - Hongyan Tao; Zhibo Han; Zhong Chao Han; Zongjin Li (Stem Cells International)
Mesenchymal stem cells (MSCs) have shown their therapeutic potency for treatment of cardiovascular diseases owing to their low immunogenicity, ease of isolation and expansion, and multipotency. As multipotent progenitors, MSCs have revealed their ability to differentiate into various cell types and could promote endogenous angiogenesis via microenvironmental modulation. Studies on cardiovascular diseases have demonstrated that transplanted MSCs could engraft at the injured sites and differentiate into cardiomyocytes and endothelial cells as well. Accordingly, several clinical trials using MSCs have been performed and revealed that MSCs may improve relevant clinical parameters in patients with vascular diseases. To fully comprehend the characteristics of MSCs, understanding their intrinsic property and associated modulations in tuning their behaviors as well as functions is indispensable for future clinical translation of MSC therapy. This review will focus on recent progresses on endothelial differentiation and potential clinical application of MSCs, with emphasis on therapeutic angiogenesis for treatment of cardiovascular diseases.